IDENTIFIKASI SEBARAN TINGKAT BAHAYA EROSI DI DAS BRANTAS (WILAYAH ADMINISTRASI KOTA SURABAYA) TAHUN 2022 - Ignatius Bennito Sianturi; Cherie Bhekti Pribadi (Jurnal Penginderaan Jauh Indonesia, 2025)
Erosion is a critical environmental degradation event that has profound implications for agricultural productivity, ecosystem stability, and sustainable development. This study aims to quantify the rate of soil erosion in various agro-ecological zones and to evaluate the effectiveness of soil conservation practices. Given that soil conservation processes require predicting the rate of erosion that occurs, erosion rate modeling was conducted. The commonly used modeling of erosion rate values is often limited to modeling the rate of erosion caused by water, such as sheet erosion, gully erosion, and several other erosions. High and uncontrolled erosion rates can lead to the loss of soil fertility and the accumulation of thick sediment in river flows, which can cause disasters such as floods and others. In this study, the determination of erosion hazards was conducted using the RUSLE (Revised Universal Soil Loss Equation) method in the Brantas River Basin (Administrative Boundary of Surabaya City). From the obtained erosion rate values, it was found that the Brantas River Basin area (Surabaya City area) on average has a “light” hazard level.